2010
DOI: 10.1111/j.1468-0009.2010.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

How an Age of Anxiety Became an Age of Depression

Abstract: Context: During the 1950s and 1960s, anxiety was the emblematic mental health problem in the United States, and depression was considered to be a rare condition. One of the most puzzling phenomena regarding mental health treatment, research, and policy is why depression has become the central component of the stress tradition since then. Methods: This article reviews statistical trends in diagnosis, treatment, drug prescriptions, and textual readings of diagnostic criteria and secondary literature. Findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 40 publications
1
42
0
14
Order By: Relevance
“…Mood disorders (MDs) such as depression and bipolar disorder are among the most common neuropsychiatric illnesses: almost 44 million Americans are affected by MDs, with twice as many women than men affected (Zender and Olshansky 2009;Gelenberg 2010;Horwitz 2010). Focusing specifically on major depression disorder (MDD), lifetime prevalence rates of approximately 17% have recently been reported (Kessler et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Mood disorders (MDs) such as depression and bipolar disorder are among the most common neuropsychiatric illnesses: almost 44 million Americans are affected by MDs, with twice as many women than men affected (Zender and Olshansky 2009;Gelenberg 2010;Horwitz 2010). Focusing specifically on major depression disorder (MDD), lifetime prevalence rates of approximately 17% have recently been reported (Kessler et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…[81] It seems important to indicate that a prior clinical study revealed that N-acetyl cysteine was ineffective as add-on therapy in improving patients' response to antidepressant drugs compared to placebo, [82] suggesting that N-acetyl cysteine could enhance patients resilience to stress, and indirectly, this may probably result in overall therapeutic outcome in depressed patients. [83] The use of drugs possessing antiinflammatory properties for depression represents a turning point in treating depression Activated inflammatory pathways have been reported to contribute to the pathogenesis of MDD, and cytokines such as tumour necrosis factor alpha was found to underlie cognitive impairment in MDD, suggesting a possible role of inflammation suppression in the treatment and remission of MDD. [6,28] One-third of patients with MDD demonstrated a significant improvement when they were treated with potent anti-inflammatory glucocorticoid dexamethasone for 4 days.…”
Section: Drug Repurposing: Principles and Techniquesmentioning
confidence: 99%
“…Without treatment, symptoms can last for weeks, months, or years. Appropriate treatment, however, can help most people who suffer from depression [10], [11]. In this paper definitionsof depression, anxiety and stress are based on the Depression Anxiety Stress Scale (DASS) by Lovibond and Lovibond [12].…”
Section: A Stress Anxiety and Depressionmentioning
confidence: 99%